A comprehensive review of stingless bee products: phytochemical composition and beneficial properties of honey, propolis, and pollen - Rozman, Azri Shahir; Hashim, Norhashila; Maringgal, Bernard; Abdan, Khalina (Multidisciplinary Digital Publishing Institute, 2022)
The stingless bee has been gaining more attention in recent years due to the uniqueness and benefits of its products. Similar to the common honeybee, stingless bees also produce honey, propolis, and pollen, which offer superior benefits for direct or indirect consumption. However, reports on the benefits of stingless bee products are scarce. This article summarises recent reports on stingless bee products. The function and application of the properties of the products such as phenolic compounds, antioxidant properties, and chemical content are elucidated. The antimicrobial properties and anticancer potential of the products are also highlighted. Future trends, potential, and uniqueness of stingless bee products are discussed. Stingless bee honey is highlighted as a superfood that exceptionally has the potential to be an active ingredient in treating cancer. Stingless bee propolis has been extensively studied for its rich beneficial chemical compounds that contribute to its antioxidant properties. Though studies on stingless bee pollen are scarce, it has been reported that it also has the potential of being a functional food.